Nonwoven fabric and nonaqueous secondary battery

By adopting non-woven fabrics with annular fiber structure, the fiber direction and the porosity are reduced, the problem of increasing fiber direction in the preparation process of existing wet non-woven fabrics is solved, low impedance and high liquid retention capabilities are achieved, and the performance of lithium-ion batteries is improved.

JP7666946B2Active Publication Date: 2025-04-22NIPPON KODOSHI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021024636
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-18
Publication Date
2025-04-22
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

During the preparation process, the fibers of existing wet non-woven fabrics are easily arranged in the direction of liquid flow, resulting in an increase in fiber direction, an increase in structural density, and a decrease in porosity, which limits the low impedance and high liquid retention ability of the battery separator.

Method used

The non-woven fabric with annular fiber structure can reduce the fiber direction and increase the porosity of the fabric by controlling the annular shape and crossing angle of the fiber, thereby achieving low impedance and high liquid retention capabilities.

Benefits of technology

Achieve high porosity and low impedance non-woven fabrics, improving the output performance, life and capacity of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666946000002
    Figure 0007666946000002
  • Figure 0007666946000003
    Figure 0007666946000003
  • Figure 0007666946000004
    Figure 0007666946000004
Patent Text Reader

Abstract

To provide a fine nonwoven fabric with a high porosity.SOLUTION: Provided is a nonwoven fabric composed of a plurality of annular shape bodies consisting of fibers.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonwoven fabric and a nonaqueous secondary battery (for example, a lithium ion secondary battery) using the nonwoven fabric as a separator. [Background technology]

[0002] Nonwoven fabrics are not only suitable for mass production and can be manufactured at low cost, but also have a variety of functions, so they are widely used in various fields such as battery separators and filters, sanitary materials, packaging materials, etc. In particular, wet-laid nonwoven fabrics, which have excellent homogeneity, are used for battery separators in nonaqueous secondary batteries such as alkaline batteries, nickel-metal hydride batteries, and lithium-ion batteries, and for filters that filter liquids and gases.

[0003] Lithium-ion batteries are widely used as power sources for electronic devices such as laptops, mobile phones, and digital cameras, and in recent years have also begun to be used as power sources for mobile vehicles such as electric and hybrid vehicles. With the development of these electronic devices and the expansion of their range of application to mobile vehicles, there is a demand for lithium-ion batteries with larger capacities, higher output, and longer life.

[0004] Focusing on the separator, which is a component of lithium-ion batteries, in order to meet the above needs, it is necessary to make the separator thinner, lower the resistance, and improve the liquid retention. In other words, there is a demand for a separator that is thin, dense, and has a high porosity, and a wet-laid nonwoven separator with a higher porosity has been proposed in place of the porous films that have been used as separators in the past (see, for example, Patent Document 1).

[0005] Meanwhile, filters are widely used in various fields. The performance required for a filter is high collection efficiency and low pressure loss. A filter with low pressure loss has the advantage of reducing energy costs during use and having a long life for the filter itself. As one means to achieve this, a thin, dense nonwoven fabric with a high porosity is required.

[0006] In other words, to further improve the performance of lithium-ion batteries and filters, nonwoven fabrics that are denser and have a higher porosity than the wet-laid nonwoven fabrics currently in practical use will be required. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6317556 Summary of the Invention [Problem to be solved by the invention]

[0008] The separator used in the above-mentioned Patent Document 1 is made of a wet-laid nonwoven fabric, which is formed by collecting a slurry, in which fibers are dispersed in a liquid, on a wire.

[0009] However, because fibers dispersed in the liquid tend to align themselves with the flow of the slurry, the proportion of fibers oriented in a specific direction increases. As a result, the fibers tend to have a dense structure, the porosity decreases, and there are limitations to reducing resistance and increasing liquid retention.

[0010] Therefore, an object of the present invention is to obtain a dense nonwoven fabric with a high porosity, and to provide a nonaqueous secondary battery using the nonwoven fabric. [Means for solving the problem]

[0011] The inventors of the present application focused on the above-mentioned fiber orientation and conducted extensive research into the configuration of a nonwoven fabric with less fiber orientation, which resulted in the invention of the present application.

[0012] The nonwoven fabric of the present invention is characterized in that the constituent fibers are of an annular shape. In such a nonwoven fabric, the fibers are less likely to be oriented and the porosity is high, resulting in low resistance and high liquid retention.

[0013] That is, the nonwoven fabric according to the first aspect of the present invention is a nonwoven fabric composed of a plurality of annular shaped bodies made of fibers. Furthermore, the annular body is a complete ring or an open ring, the distance between the start point and the end point of the annular body is less than 64% of the fiber length when the fiber is stretched in a straight line, the fiber length is 5 μm or more and 1500 μm or less, and the nonwoven fabric has a porosity of 70% or more and 90% or less.

[0014] In addition, the nonwoven fabric according to the second aspect of the present invention is a nonwoven fabric in which a plurality of annular-shaped bodies made of fibers are overlapped in the left-right and up-down directions when viewed in a plane, and at the overlapping portions of the annular-shaped bodies, the fibers constituting the annular-shaped bodies cross at a smaller crossing angle of 30° or more and 90° or less.

[0015] The nonwoven fabric according to a third aspect of the present invention is a nonwoven fabric in which the plurality of annular shaped bodies are formed from fibers differing in at least one of fiber diameter and fiber length.

[0016] The nonwoven fabric according to the fourth aspect of the present invention is a nonwoven fabric in which the multiple annular bodies are composed of annular bodies formed by thick, long fibers and annular bodies formed by thin, short fibers.

[0019] The present invention Fifth The nonwoven fabric according to the present invention is characterized in that the thickness of the nonwoven fabric is 3 μm or more and 20 μm or less.

[0020] The present invention Sixth The non-aqueous secondary battery according to the present invention is Fifth The nonwoven fabric according to the present invention is disposed between a positive electrode and a negative electrode. Effect of the Invention

[0021] According to the present invention, a dense nonwoven fabric having a high porosity can be obtained. Therefore, if this nonwoven fabric is used as a separator, it will become a thin separator with low resistance and high electrolyte retention, which can contribute to increasing the output, life, and capacity of non-aqueous secondary batteries such as lithium ion secondary batteries. [Brief description of the drawings]

[0022] [Figure 1]FIG. 1 is a schematic diagram of a lithium ion secondary battery. [Diagram 2] FIG. 2 is an enlarged view of a portion of the separator in FIG. [Diagram 3] 1 is an electron microscope photograph of the nonwoven fabrics of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the present invention will be described in detail.

[0024] The nonwoven fabric of the present invention is composed of a plurality of annular fibrous bodies with the aim of obtaining a dense nonwoven fabric with a high porosity. The non-aqueous secondary battery of the present invention is constructed by disposing the non-woven fabric of the present invention between a positive electrode and a negative electrode.

[0025] In the present invention, the "annular shaped body" is basically a ring-shaped body (such as a toroid), but does not have to be a perfect ring, and also includes an open ring (C-shape), and the shape of the ring is not limited to a circle, but also includes an ellipse or a shape modified from a circle. In other words, the "annular shaped body" refers to a body in which the distance connecting the start point and end point of the constituent fibers is less than a predetermined percentage (e.g., less than 64%) of the fiber length when the fibers are stretched in a straight line.

[0026] Fig. 1 is a schematic diagram of a lithium ion secondary battery as an example of a non-aqueous secondary battery using a nonwoven fabric according to an embodiment of the present invention as a separator. Fig. 1 is a perspective view showing a part of the lithium ion secondary battery in an expanded form.

[0027] 1, the case 1 is a box-shaped case with an open top, and is made of, for example, iron. Inside the case 1 is a battery element 2, which has a structure in which a strip-shaped positive electrode 3 and a strip-shaped negative electrode 4 are wound with a strip-shaped separator 5 interposed therebetween.

[0028] In this embodiment, since the battery element 2 is a lithium ion secondary battery, the battery element 2 has a structure in which lithium ions are contained in at least one of the positive electrode 3 and the negative electrode 4. In addition, the battery element 2 holds an electrolyte. A lid 6 made of an insulating material such as resin is attached to the opening on the top surface of the case 1. The lid 6 is provided with a safety valve 7 and a positive terminal 8.

[0029] The safety valve 7 opens when the pressure inside the case 1 rises to or exceeds a predetermined value, and discharges the pressure inside the case 1 to the outside of the case 1. Moreover, the positive electrode terminal 8 serves as a + terminal of the lithium ion secondary battery, and this positive electrode terminal 8 and the positive electrode 3 are electrically and mechanically connected within the case 1 . Furthermore, within the case 1, the negative electrode 4 and the inner surface of the case 1 are electrically and mechanically connected, and the case 1 serves as the negative terminal of the lithium ion secondary battery.

[0030] The separator 5 used in this embodiment is in the form of a long strip. Fig. 2 is an enlarged view of a portion of the separator 5 in Fig. 1. The right diagram of Fig. 2 is an enlarged plan view of a portion of the separator 5. The left diagram of Fig. 2 is an enlarged view of the area surrounded by a dashed line in the right diagram of Fig. 2.

[0031] The separator of this embodiment is characterized in that the nonwoven fabric is composed of a plurality of annular shaped bodies 9, 10 made of fibers, as shown in Fig. 2. This configuration makes it difficult for the fibers to be oriented, and the fibers do not form a dense structure, resulting in a dense nonwoven fabric with high porosity.

[0032] Furthermore, it is preferable that the multiple annular shaped bodies 9, 10 overlap in the left-right and up-down directions in the plan view shown in Fig. 2, and that in the overlapping portions between the annular shaped bodies, the smaller crossing angle between the fibers constituting the annular shaped bodies is between 30° and 90°. With this configuration, the overlapping portions between the annular shaped bodies 9, 10 are reduced, and a dense nonwoven fabric with a higher porosity can be obtained. In Fig. 2, the fibers overlap with each other at smaller crossing angles such as θ1 and θ2 in the left diagram, which are 30° to 90°. The crossing angles θ1 and θ2 in the left diagram are about 70° to 80°, which satisfies the range of 30° to 90°. If the crossing angle is less than 30°, the overlapping portions of the annular bodies will increase, resulting in a smaller void ratio.

[0033] Nonwoven fabrics with this structure are obtained by spraying a slurry containing fibers onto a substrate. The slurry breaks into fine droplets as a result of the spraying. At this time, fibers longer than the diameter of the droplets deform into a round shape that conforms to the droplets, i.e., they adhere to the substrate in a ring-shaped form. After spraying, the fabric is dried and peeled off from the substrate.

[0034] 1, the separator 5 made of nonwoven fabric is configured separately from the electrodes (positive electrode 3 and negative electrode 4), but the slurry may be sprayed onto the positive electrode 3 or the negative electrode 4, or onto both of them 3, 4, to form the nonwoven fabric directly on the electrodes. Similarly, when used as a filter, the nonwoven fabric may be formed directly on a coarse filter or the like.

[0035] The length of the fibers that become annular bodies depends on the diameter of the droplets formed by spraying. The diameter of the droplets depends on the spraying method, the viscosity of the slurry, etc., but it is probably difficult to make it smaller than 5 μm. Also, because fibers that are too long can cause spits (coarse particles) during spraying, the length of the fibers is preferably 1500 μm or less. In other words, the length of the fibers that become annular bodies should be 5 μm or more and 1500 μm or less.

[0036] The fibers constituting the nonwoven fabric are preferably formed from fibers having different diameters and / or lengths. If the diameters and lengths of the fibers are different, the sizes of the annular bodies formed will also be different. As a result, the small annular bodies form a web so as to fill the gaps between the large annular bodies, and a denser nonwoven fabric with a higher porosity can be formed compared to a single fiber.

[0037] To further explain the above configuration, for example, in Fig. 2, the separator is formed by an annular body 9 made of thick and long fibers and an annular body 10 made of thin and short fibers. In this embodiment, thick fibers refer to fibers having a fiber diameter of, for example, 1 µm or more, and thin fibers refer to fibers having a fiber diameter of, for example, less than 1 µm.

[0038] As shown in Figure 2, the thick fibers are longer than the thin fibers. Therefore, the diameter of the annular body 9 made of the thick fibers is larger than the diameter of the annular body 10 made of the thin fibers. With this configuration, the annular body 9 formed of the thick and long fibers maintains strength, and the annular body 10 formed of the thin and short fibers forms a dense web, so that the mechanical strength of the nonwoven fabric can be increased while maintaining density and a high porosity.

[0039] In addition, the number of annular shaped bodies 10 made of thin fibers is greater than the number of annular shaped bodies 9 made of thick fibers. In this configuration, the number of annular shaped bodies 10 made of thin fibers is greater, so that the denseness of the separator can be improved.

[0040] Another characteristic of this embodiment is that not only annular shaped bodies 10 made of thin fibers but also annular shaped bodies 9 made of thick fibers are mixed together, which increases the mechanical strength of the separator 5 and, as a result, makes it extremely suitable as a separator for lithium ion batteries.

[0041] As such fibers, fibrillable regenerated cellulose fibers are suitable, because the distribution of fiber diameter and fiber length can be adjusted by beating. The beaten fiber slurry contains fibers of various diameters and lengths, from thick and long fibers to thin and short fibers. Since the distribution of fiber diameter and fiber length can be adjusted by beating, it is easy to obtain nonwoven fabrics with improved mechanical strength while maintaining denseness and high porosity. Of course, other fibrillable fibers can be used, or cut fibers of uniform length can be used depending on the required density, or two or more types of fibers of different thicknesses or lengths can be mixed, or cut fibers can be mixed with fibrillable fibers.

[0042] The means for beating the fibers can be any existing means, such as a single disc refiner (SDR), double disc refiner (DDR), beater, or homomixer. In addition, the underwater head-on collision method or water jet method can also be selected. The degree of beating can be adjusted according to the pore size of the desired nonwoven fabric.

[0043] The method of spraying the slurry can be a two-fluid nozzle (air spray) using compressed gas, a pressurized nozzle (airless spray), an electrostatic spray, a rotary atomizer using a rotating disk, etc. Among these, the two-fluid nozzle is preferred because it can reduce the diameter of the droplets. The concentration of the slurry to be sprayed can be adjusted by the spraying method and conditions. If necessary, additives such as a viscous agent, a dispersant, an antifoaming agent, and a binder may be added to the slurry.

[0044] The porosity of the nonwoven fabric is preferably 70% or more and 90% or less, which results in a nonwoven fabric with low resistance, high liquid retention, and low pressure loss, making it suitable for use as a separator or filter for nonaqueous batteries. If the porosity is too low, the significance of the present invention is diminished, whereas if the porosity is too high, problems may occur in terms of strength and shielding properties.

[0045] The thickness of the nonwoven fabric is preferably 3 μm or more and 20 μm or less, which results in a nonwoven fabric with low resistance and low pressure loss, and is suitable for use as a separator or filter for a nonaqueous battery. If it is too thin, it becomes difficult to ensure shielding properties, and if it is too thick, the resistance becomes high.

[0046] Furthermore, by forming a non-aqueous secondary battery in which the non-woven fabric according to the present invention, which is made up of a plurality of annular shaped bodies, is placed between a positive electrode and a negative electrode, a non-aqueous battery with large capacity, high output, and long life can be obtained.

[0047] Hereinafter, specific examples and comparative examples of the nonwoven fabric according to the present invention and a nonaqueous secondary battery including the nonwoven fabric as a separator will be described in detail.

[0048] First, a nonwoven fabric according to an embodiment of the present invention was produced and each characteristic was examined. The characteristics were measured under the following conditions and by the following method.

[0049] [Thickness] The thickness of the nonwoven fabric was measured using a micrometer as specified in "JIS C 2300-2 'Cellulose paper for electrical use - Part 2: Test methods' 5.1 Thickness" in "5.1.1 Measuring instruments and measuring methods a) When using an outside micrometer" and the method of folding the paper into 10 sheets as specified in "5.1.3 When measuring thickness by folding the paper". Note that, for Example 4 described later, the thickness of the electrode / nonwoven fabric assembly and the electrode were each measured, and the thickness of the nonwoven fabric was calculated from the difference between the thicknesses.

[0050] [Basic weight] The basis weight of the nonwoven fabric was measured according to the method specified in "JIS C 2300-2 'Cellulose paper for electrical use - Part 2: Test methods' 6 Basis weight." Note that, for Example 4 described later, the basis weights of the electrode / nonwoven fabric assembly and the electrode were measured separately, and the basis weight of the nonwoven fabric was calculated from the difference between the two.

[0051] [Porosity] The porosity of the nonwoven fabric was calculated using the following formula. Porosity (%)=100-(W / ρ) / T×100 (Formula 1) Here, W is the basis weight of the nonwoven fabric (g / m 2 ) and ρ is the fiber density (g / cm 3 ) and T was used to calculate the porosity, using the thickness of the nonwoven fabric (μm). The above formula is for when one type of fiber is used, but if there are multiple types of fiber, change the (W / ρ) part to one that takes into account the amount and density of each fiber. For example, if there are two types of fiber, the formula is as follows: (W / ρ)=(W×R1 / 100 / ρ1+W×R2 / 100 / ρ2) (Formula 2) Here, W is the basis weight of the nonwoven fabric (g / m 2 ), R1 and R2 are the blending ratios (%) of each fiber, and ρ1 and ρ2 are the densities (g / cm 3 )

[0052] Next, a lithium ion secondary battery was fabricated using the obtained nonwoven fabric as a separator, and each characteristic was examined. The fabrication of the battery and the measurement of each characteristic were carried out as follows.

[0053] [Method of manufacturing a lithium-ion battery] A lithium cobalt oxide electrode for lithium ion secondary batteries was used as the positive electrode material, and a graphite electrode was used as the negative electrode material, and the electrodes were wound with a separator to obtain a lithium ion secondary battery element winding. The element winding was stored in a cylindrical case with a bottom, and an electrolyte solution in which lithium hexafluorophosphate was dissolved as an electrolyte in a mixed solvent of ethylene carbonate and diethyl carbonate was injected, and the case was sealed with a press. In this way, a lithium ion secondary battery with a rated voltage of 3.7 V, a rated capacity of 3000 mAh, a diameter of 18 mm, and a height of 65 mm was produced. Note that only in Example 4 described later, a lithium ion secondary battery with a rated capacity of 3300 mAh was produced. This is because the separator was made thinner, making it possible to fit more active material in the case.

[0054] [High rate discharge characteristics] The high-rate discharge characteristics of lithium-ion secondary batteries were measured as a ratio of the discharge capacity at 20 ItA to the rated capacity in accordance with "6.3.3 High-rate discharge performance" specified in "JIS C 8715-1 'Industrial lithium secondary batteries and battery systems - Part 1: Performance requirements'".

[0055] [AC internal resistance] The AC internal resistance of the lithium-ion secondary battery was measured in accordance with "6.5.2 AC internal resistance" specified in "JIS C 8715-1 'Industrial lithium secondary battery cells and battery systems - Part 1: Performance requirements'".

[0056] [Charge / discharge cycle durability] The charge / discharge cycle durability of the lithium-ion secondary battery was measured in accordance with "6.6.1 Charge / discharge cycle durability" specified in "JIS C 8715-1 'Industrial lithium secondary battery cells and battery systems - Part 1: Performance requirements'". The charge / discharge current value was 1.0 ItA.

[0057] Example 1 A slurry of fibrillable regenerated cellulose fibers was prepared by beating DDR with a homomixer to a concentration of 1%. This slurry was then sprayed onto the substrate PET film at an air pressure of 0.3 MPa using an air spray gun for painting, dried in an oven at 80°C, and peeled off from the substrate to produce a 4.5 g / m2 basis weight. 2 A nonwoven fabric having a thickness of 15 μm and a porosity of 80.0% was obtained. A lithium ion secondary battery was produced using this nonwoven fabric as a separator, and the battery characteristics were measured.

[0058] Comparative Example 1 The fibrillable regenerated cellulose fiber is beaten in a DDR and made into fourdrinier paper, resulting in a basis weight of 7.4 g / m 2 A nonwoven fabric having a thickness of 14.0 μm and a porosity of 64.8% was obtained. A lithium ion secondary battery was produced using this nonwoven fabric as a separator, and the battery characteristics were measured.

[0059] Example 2 A 5.7 g / m2 sheet was prepared in the same manner as in Example 1, except that the treatment time in the homomixer was longer than in Example 1. 2 A nonwoven fabric having a thickness of 14.5 μm and a porosity of 73.8% was obtained. A lithium ion secondary battery was produced using this nonwoven fabric as a separator, and the battery characteristics were measured.

[0060] Example 3 A 2.8 g / m2 sheet was prepared in the same manner as in Example 1, except that the treatment time in the homomixer was shorter than that in Example 1. 2 A nonwoven fabric having a thickness of 14.5 μm and a porosity of 87.1% was obtained. A lithium ion secondary battery was produced using this nonwoven fabric as a separator, and the battery characteristics were measured.

[0061] Comparative Example 2 A 1.5 g / m2 spunbonded ... 2 A nonwoven fabric having a thickness of 14.0 μm and a porosity of 92.9% was obtained. A lithium ion secondary battery was produced using this nonwoven fabric as a separator, but a short circuit occurred and the battery did not function.

[0062] Example 4 The same method as in Example 1 was used, except that the amount of slurry sprayed was reduced from that in Example 1 and sprayed directly onto the negative electrode, resulting in a slurry having a basis weight of 2.0 g / m. 2 A nonwoven fabric separator with a thickness of 6.5 μm and a porosity of 79.5% was formed directly on the negative electrode. A lithium-ion secondary battery was then fabricated using the resulting negative electrode and separator combination, and the battery characteristics were measured. In addition, because the separator could be made thinner, it became possible to fit more active material into the case, and the rated capacity of the battery could be increased to 3300 mAh.

[0063] Table 1 shows a list of the characteristics of the nonwoven fabrics of each of the examples and comparative examples, and the characteristics of the lithium-ion batteries using them as separators. Electron microscope photographs of the nonwoven fabrics of Example 1 and Comparative Example 1 are shown in FIG.

[0064] [Table 1]

[0065] By comparing the nonwoven fabrics of Example 1 and Comparative Example 1 shown in FIG. 3, the following was found. In the nonwoven fabric of Example 1 (the present invention), the fibers have a ring-shaped configuration with no observed orientation, and at the overlapping portions of the ring-shaped bodies, the fibers that make up the ring-shaped bodies overlap with the smaller crossing angle between 30° or more and 90° or less, resulting in a highly porous structure. In contrast, in the nonwoven fabric of Comparative Example 1 (conventional), the fibers oriented in the vertical direction of the photograph are prominent, and the portions where the fibers are in close contact with each other and block the gaps are prominent. This difference affects the porosity, with the porosity of the nonwoven fabric of Example 1 being 80%, which is greater than the porosity of 64.8% of the nonwoven fabric of Comparative Example 1. It can be seen that by using a nonwoven fabric having the configuration of the present invention, a nonwoven fabric with a high porosity is obtained.

[0066] From the results of Examples 1 to 3 and Comparative Examples 1 and 2 in Table 1, it is understood that by using the nonwoven fabric with high porosity of the present invention as a separator, a lithium ion secondary battery with excellent high-rate discharge characteristics, AC internal resistance, and charge / discharge cycle durability can be realized. It is also understood that the porosity range is preferably 70% or more and 90% or less. If the porosity is lower than 70%, the difference with conventional nonwoven fabrics becomes small, and the significance of the present invention is diminished, and if the porosity is higher than 90%, the shielding properties cannot be maintained.

[0067] From Example 4, it is found that the thickness of the separator can be thinned to 6.5 μm, and by thinning the separator thickness, the capacity of the lithium ion secondary battery can be increased. As mentioned above, the thickness of the separator is preferably 3 μm or more. Although we will not explain the upper limit of the thickness with examples, it is preferably 20 μm or less. If the thickness exceeds 20 μm, the resistance becomes high.

[0068] As described above, according to the present invention, a dense nonwoven fabric with high porosity can be obtained. When this nonwoven fabric is used as a separator, a thin separator with low resistance and high electrolyte retention rate can be obtained, which can contribute to increasing the output, life span, and capacity of nonaqueous secondary batteries such as lithium ion secondary batteries. [Explanation of symbols]

[0069] 1 case, 2 battery element, 3 positive electrode, 4 negative electrode, 5 separator, 6 lid, 7 safety valve, 8 positive electrode terminal, 9 annular body (made of thick fibers), 10 annular body (made of thin fibers)

Claims

1. A nonwoven fabric composed of a plurality of annular shaped bodies made of fibers, The annular body is a complete ring or an open ring, and the distance between the start point and the end point of the fiber constituting the annular body is less than 64% of the fiber length when the fiber is stretched linearly; The length of the fiber is 5 μm or more and 1500 μm or less, The nonwoven fabric has a void ratio of 70% or more and 90% or less. Nonwoven fabric.

2. The nonwoven fabric of claim 1, wherein the multiple annular shaped bodies made of fibers are overlapped in the left-right and up-down directions when viewed in a plane, and at the overlapping portions of the annular shaped bodies, the fibers constituting the annular shaped bodies are overlapped in such a manner that the smaller crossing angle between the fibers is 30° or more and 90° or less.

3. 3. The nonwoven fabric according to claim 1, wherein the plurality of annular shaped bodies are formed from fibers having at least one of a fiber diameter and a fiber length different from each other.

4. 4. The nonwoven fabric according to claim 3, wherein the plurality of annular bodies are composed of annular bodies formed of thick and long fibers and annular bodies formed of thin and short fibers.

5. The nonwoven fabric according to any one of claims 1 to 4, wherein the nonwoven fabric has a thickness of 3 µm or more and 20 µm or less.

6. A non-aqueous secondary battery comprising the nonwoven fabric according to any one of claims 1 to 5 disposed between a positive electrode and a negative electrode.

Citation Information

Patent Citations

  • JP1973019865B1

  • Manufacture of semiconductor device

    JP1988017556A

  • Nonwoven fabric mat for filter

    JP1999226329A

  • Substrate for lithium secondary battery, and separator for lithium secondary battery

    JP2012195162A

  • Modified cellulose fiber, dispersion liquid, porous film, electricity storage element and method of manufacturing porous film

    JP2019116705A